Proximate composition, nutritional attributes and mineral composition of Peperomia pellucida L. (ketumpangan air) grown in Malaysia - Ooi, Der Jiun; Iqbal, Shahid; Ismail, Maznah (MDPI, 2012)
This study presents the proximate and mineral composition of Peperomia pellucida L., an underexploited weed plant in Malaysia. Proximate analysis was performed using standard AOAC methods and mineral contents were determined using atomic absorption spectrometry. The results indicated Peperomia pellucida to be rich in crude protein, carbohydrate and total ash contents. The high amount of total ash (31.22%) suggests a high-value mineral composition comprising potassium, calcium and iron as the main elements. The present study inferred that Peperomia pellucida would serve as a good source of protein and energy as well as micronutrients in the form of a leafy vegetable for human consumption.